Knowledge Sharing : A Review of the Literature - Cummings, Jeffrey (World Bank, Washington, DC, 2014)
A successful knowledge-sharing effort requires a focus on more than simply the transfer of the specific knowledge. Instead, many of the activities to be undertaken need to focus on structuring and implementing the arrangement in a way that bridges both existing and potential relationship issues, and examining the form and location of the knowledge to ensure its complete transfer. In other words, while the activities used to share knowledge, such as document exchanges, presentations, job rotations, etc., are important, overcoming the factors that can impede, complicate and even harm knowledge internalization are equally important in determining the ultimate results of a knowledge-sharing effort. Accordingly, any evaluations of the Bank s knowledge-sharing efforts need to incorporate assessments of its use of activities related to understanding the form and embedded knowledge, establishing and managing appropriate administrative structures, and facilitating the transfer of the knowledge.